Analisis Potensi Kurikulum Merdeka Dalam Meningkatkan Kualitas Pendidikan - aisha artanti; kittin andila; nur anita; rena revita (CONSISTAN (Jurnal Tadris Matematika), 2025)
Through a literature review, this study attempts to evaluate the ability of the Merdeka Curriculum to improve the standard of Indonesian education. Through the use of project-based learning, varied learning, and strengthening the Pancasila Student Profile, the Merdeka Curriculum provides a flexible, contextual, and learner-centered educational approach. The results of the study show how well this program can develop students' character and improve their 21st century skills. However, there are still a number of obstacles in its implementation, including public opinion, infrastructure inequality, and teacher readiness. Therefore, to achieve successful implementation of the curriculum in a fair and sustainable manner, a plan is needed that strengthens teacher competence, comprehensive socialization, and cross-sectoral assistance.